Studi Komparasi Payback Framework Dan Grc Sebagai Kerangka Kerja Evaluasi Program - Agustifa, Filda Nurria; Armono, Haryo Dwito; Taufik, Tatang A. (Riviera Publishing, 2025)
This study compares the Payback Framework and the Governance, Risk Management, and Compliance (GRC) framework as evaluation tools for research funding programs. The Payback Framework, developed in 1994 by Buxton and Hanney, focuses on assessing the impact of health research, encompassing knowledge creation, policy influence, and economic benefits. On the other hand, the GRC framework emphasizes risk management, governance, and regulatory compliance, ensuring that programs are managed effectively within regulatory boundaries. This comparative analysis highlights the strengths and weaknesses of both frameworks, examining their applicability to different types of programs. The Payback Framework is well-suited for research programs that require long-term impact assessment, particularly in healthcare and social sciences. Meanwhile, the GRC framework is more appropriate for sectors with stringent compliance requirements, such as finance and healthcare. This study provides insights into the choice of evaluation frameworks based on program objectives, organizational needs, and available resources..